Impact of over 6 months of digital hearing aid usage on auditory working memory in acquired severe to profound hearing loss - Arun K. Yadav; Amra Ahsan; Vijay Kumar; Arun Banik (Journal of Family Medicine and Primary Care)
Introduction: Hearing amplification devices provide ample auditory input that can help to decrease the cognitive strain caused by hearing loss. Depending on the kind and severity of hearing loss, using hearing aids has variable effects on auditory working memory. This study looked into the auditory working memory capacity after using hearing aids for more than 6 months. Method: Sixty individuals of a mean age of 53.4 ± 6.07 years with severe to profound hearing loss in the age range of 40–60 years participated. Out of them, 30 individuals with a mean age of 53.5 ± 6.7 were using digital hearing aids and another 30 individuals with a mean age of 53.3 ± 5.4 years were not using a hearing aid. Forward and backward digit span task (DST) and Mini-Mental Status Examination (MMSE) were investigated to estimate the auditory working memory capacity. Results: Mean MMSE scores of those individuals with severe to profound hearing loss (53.3 ± 5.43) using (HAU) a hearing aid (25.7 ± 2.97) and individuals not using (NHAU) a hearing aid (22.1 ± 5.11) were compared across each other. The result revealed that the mean MMSE score of HAU was significantly higher than the mean score of NHAU. The mean DST (forward, backward, and total) score of HAU (6.40 ± 1.47) was cosiderably higher than the mean score of NHAU (5.33 ± 1.12). Conclusion: Results showed that mean MMSE and DST scores were higher in the HAU category, but when compared across the gender, no statistical differences were observed. The change in auditory working memory and other cognitive abilities were attributed to the usage duration of the hearing aids.